Successful Outcome after Laparoscopic Management of Heterotopic Pregnancy - Sultana, Nargis; Tariquzzaman, Md; Sultana, Nadira; Akter, Rumana; Tariq, Nahin Sanjid Bin (Journal of Current and Advance Medical Research, 2025)
Background: Heterotopic pregnancy refers to the simultaneous occurrence of intrauterine and extrauterine (usually tubal) gestations, a rare but potentially life-threatening condition. Its management poses significant clinical challenges, requiring prompt diagnosis and individualized treatment to preserve maternal health and, if possible, the intrauterine pregnancy. Objective: The aim of this study was to investigate the clinical outcome of laparoscopic surgery for women with heterotopic pregnancy. Methodology: This was a retrospective observational study to see the clinical outcome of 8 patients with intrauterine and tubal pregnancy undergoing laparoscopic operation. The products of ectopic pregnancy were removed laparoscopically. Results: The median operation time was 12 minutes, and the average blood loss was 25 ml. There were no postoperative complications. The wounds recovered well in all cases. Among these women, 6 delivered at term whereas 2 failed to continue their pregnancies, one had an abortion after 8 days of the surgery and another one had an abortion due to preterm premature rupture of the membrane at 15 gestational weeks. Conclusion: Laparoscopic surgery is an effective technique in successful management of heterotopic pregnancy. Journal of Current and Advance Medical Research, July 2024;11(2):68-72